Pengamatan Jangka Panjang dan Intervensi Anak dengan Rakhitis dan Hipovitaminosis D - Toni Kurniawan; Eka Agustia Rini; Asrawati Asrawati (Faculty of Medicine, Universitas Andalas, 2024)
Rickets is associated with impaired calcium and phosphate homeostasis, which can lead to short stature and joint deformities. Nutritional rickets results from deficiencies of vitamin D, calcium and phosphate. Vitamin D regulates calcium and phosphorus in the blood, if there is a deficiency of vitamin D it results in inadequate mineralization of osteoid produced by osteoblasts. It is important to ensure adequate vitamin D supplementation in nutritional rickets and rule out vitamin D deficiency in other forms of rickets, which may hinder healing of rickets. Medical rehabilitation can improve functional independence by reducing pain and improving joint mobility, muscle strength, endurance, and gait in rickets patients.